Determinasi Nilai Perusahaan: Likuiditas, Struktur Modal dan Profitabilitas pada Perusahaan Konstruksi dan Bangunan - Widyaningsih, Ika Utami (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2023)
This study aims to analyze the effect of liquidity, capital structure, and profitability on the firm value of Construction and Buildings Sector Companies. Liquidity measured by current ratio, capital structure measured by debt to equity ratio, profitability measured by the return on equity and firm value measured by price earning ratio. The sample used in this research is 8 companies with a purposive sampling method. The data analysis technique used is panel data regression model. The results show that partially current ratio has no effect on the price earning ratio, while the debt to equity ratio have a negative effect on firm value. And profitability have a positive effect on firm value. Simultaneously the current ratio, debt to equity ratio and return on equity affect to the firm value.